Extended state observer-based composite-system control for trajectory tracking of underactuated AUVs. (July 2021) - Lei, Ming; Li, Ye; Pang, Shuo
Highlights: A novel control law for trajectory tracking of underactuated AUVs is given, by combining the high gain technique, singular perturbation theory, backstepping technique and composite-system method. Abstract: In this paper, an alternative design method is presented for the horizontal trajectory tracking of underactuated autonomous underwater vehicles (AUVs) subject to unknown internal and external disturbances. In the guidance loop, a kinematic control law of the desired surge speed and trajectory angle is derived. To meet the previous convergence requirement, a kinetic control law is developed. It consists of two terms: the disturbance rejection and the stabilizing controller. The former is given by using an extended state observer (ESO) based on the high gain technique. In this process, the singular perturbation theory is applied to analyze the extended state system via order reduction. Then the latter is designed in the reduced model independently, in term of the backstepping technique and a composite-system method. Moreover, this paper also proves that the proposed controller makes the closed-loop system asymptotically stable. Finally, simulation results are presented to illustrate the control performance.